PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN PRODUK UMKM DI KECAMATAN BREBES - Apriyani, Apriyani; Permana, Desy Intan (Jurnal Strategik, 2023)
The marketing performance of MSMEs that lags behind other business actors, makes it increasingly difficult for MSMEs to develop their businesses. Market orientation and product innovation are the focus that must be worked on so that marketing performance is higher. The purpose of this study was to determine and analyze the effect of market orientation and product innovation on marketing performance in MSMEs in Brebes District. The variables of this study are market orientation, product innovation, and marketing performance. The population of this study was all MSMEs in Padasugih Village, Brebes District with a total of 131 business actors. The sample in this study was calculated using the Slovin formula with a total of 99 respondents. The method in collecting research data was using a questionnaire by giving it to business actors in Padasugih Village, Brebes District. To analyze the data in this study, namely using the classical assumption test, F test, t test and determination correlation test, but previously the validity and reliability of the data must be tested first. The results of this study indicate that market orientation has a positive and significant effect on marketing performance in Brebes District. Product innovation has a positive and significant effect on marketing performance in Brebes District. Market orientation and product innovation have a positive and significant effect simultaneously on marketing performance in Brebes District. Keywords: market orientation, product innovation, marketing performance